Interrelations between match characteristics, field- and laboratory tests in youth elite basketball players - Brink, M. S.; Fiechter, H.; Otten, E.; Lemmink, K. A. P. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: To develop an effective training program, objective information about the physiological strengths and weaknesses of basketball players is needed. These physiological capacities are usually investigated using field- or laboratory tests. It is assumed that these tests reflect the physical demands of matches (Impellizzeri & Marcora 2009). The purpose of the present study was to determine if field tests and laboratory tests are related to match characteristics in youth elite basketball players. Methods: Time motion analyses of four quarters out of two matches were carried out for twenty-one youth elite basketball players (age 17,50 ± 1,56 years, body mass 82,50 ± 9,75 kg, height 192,13 ± 7,70 cm and body fat 9,21 ± 3,50 %). Positional data was collected based on 10 Hz top-view video footage, using semi-automatic tracking software. Relative time spent on standing/walking, jogging, low speed running, high speed running and sprinting was calculated. In addition, players performed the Interval Shuttle Sprint Test (ISST), Interval Shuttle Run Test (ISRT) (Lemmink et al., 2004), a 30s Wingate test (Bar-Or, O 1987) and a treadmill test to determine maximal oxygen uptake (VO2max). Interrelations between all exercise modes were examined using Pearson correlation coefficients. Results: Players` peak and total sprint time on the ISST was 8,5 ± 0,29s and 26,3 ± 0,91s respectively and they completed 106,5 ± 24,72 runs on the ISRT. Wingate peak power was 17,1 ± 2,22 W/kg and players` VO2max was 56,7 ± 4,87 ml/min/kg. Relative sprint time during matches was related to peak and total sprint time of the ISST (r = 0,63 and r = 0,59; p < 0,05 respectively). Furthermore, ISRT performance was associated with higher VO2max (r = 0,61; p < 0,05). Although trends were found for the relation between match characteristics and ISRT and for the ISST and the Wingate test, none of these correlations were significant. Discussion: This study provided evidence that the ISST, as an intermittent field tests, can be used to test the sprinting capacities of basketball players. The results did not directly support the use of the ISRT as a specific aerobic running test in basketball players but trends were found. Furthermore, it was found that, the anaerobic 30s Wingate test and aerobic VO2max test, are not related to match characteristics.